Philippines : Selected Issues. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 1998)
This Selected Issues paper reviews the economic development in the Philippines during the 1990s. Growth, which virtually came to a halt in the early 1990s, picked up in 1993 and accelerated steadily to almost 7 percent by end-1996, fueled by an expansion in exports and investment. At the same time, the fiscal position strengthened, inflation was successfully brought down to single digits, and with large capital inflows, particularly in 1996, gross international reserves rose to record levels. This reversal of economic fortunes was largely the result of major reforms undertaken in the past decade.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet